Evaporative water loss, relative water economy and evaporative partitioning of a heterothermic marsupial, the monito del monte (Dromiciops gliroides) - Withers, Philip; Cooper, Christine; Nespolo, R. (The Company of Biologists Ltd., 2012)
We examine here evaporative water loss, economy and partitioning at ambient temperatures from 14 to 33°C for the monito delmonte (Dromiciops gliroides), a microbiotheriid marsupial found only in temperate rainforests of Chile. The monito's standard evaporative water loss (2.58 mg g–1 h–1 at 30°C) was typical for a marsupial of its body mass and phylogenetic position. Evaporative water loss was independent of air temperature below thermoneutrality, but enhanced evaporative water loss and hyperthermia were the primary thermal responses above the thermoneutral zone. Non-invasive partitioning of total evaporative water loss indicated that respiratory loss accounted for 59–77% of the total, with no change in respiratory loss with ambient temperature, but a small change in cutaneous loss below thermoneutrality and an increase in cutaneous loss in and above thermoneutrality. Relative water economy (metabolic water production/evaporative water loss) increased at low ambient temperatures, with a point of relative water economy of 15.4°C. Thermolability had little effect on relative water economy, but conferred substantial energy savings at low ambient temperatures. Torpor reduced total evaporative water loss to as little as 21%of normothermic values, but relative water economy during torpor was poor even at low ambient temperatures because of the relatively greater reduction in metabolic water production than in evaporative water loss. The poor water economy of the monito during torpor suggests that negative water balance may explain why hibernators periodically arouse to normothermia, to obtain water by drinking or via an improved water economy.